Copeptin levels and invasive hemodynamics in patients with advanced heart failure. (30th July 2018) - Balling, Louise; Goetze, Jens Peter; Jung, Mette Holme; Rossing, Kasper; Boesgaard, Soeren; Gustafsson, Finn
Aim: Arginine vasopressin is a potent vasoconstrictory hormone and arginine vasopressin release is upregulated in heart failure (HF). The aim of this study was to evaluate if copeptin (the C-terminal part of provasopressin) is related to invasive hemodynamics in HF.Methods & results: Right heart catheterization was performed in patients with advanced HF referred for evaluation for heart transplantation. Sixty-five patients (mean age 54 ± 12 years, left ventricular ejection fraction 19 ± 8% and median copeptin levels of 16.7 pmol/l (interquartile range: 11–30 pmol/l) were included. In multivariate analysis, increased levels of log (copeptin) were associated with a reduced CI (r = 0.65 and p = 0.04).Conclusion: Increased copeptin levels in plasma are associated with hemodynamic parameters obtained at right heart catheterization in patients with HF, in particular-reduced cardiac index. Copeptin could be a useful biomarker for abnormal resting hemodynamics in HF.